Update on Hand-Held X-Ray Devices in Dentistry: a Literature Review - Barba Ramírez, Lucía; Cascante-Sequeira, Deivi (Odovtos - International Journal of Dental Sciences, 2021)
In the last two decades, the use of portable intraoral X-ray devices, stabilized by the operator, has increased. While all radiographic devices present an inherent risk from ionizing radiation, improper use of portable devices can increase operator exposure. Use of portable devices on a tripod or powered from a protected area is recommended. However, in highly justified cases, for using without these accessories, recommendations should be followed to reduce operator exposure. Because radioprotection is essential when using X-rays, fixed dental radiographic devices should be favored over portable equipment since the first provides a lower radiation dose to the operator.